2011
DOI: 10.1111/j.1470-6431.2010.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of environmental sustainability issues in consumers' choice of major household appliances in South Africa

Abstract: Although not regarded as the major culprits in terms of the degradation of the world's resources, consumers in developing countries such as South Africa should be encouraged to realize their potential contribution to save our planet. This research investigated consumers' prioritization of product choice criteria in a prominent product category, i.e. major household appliances, to determine and describe how consumers could be encouraged to accept the principles of pro‐environmental product choice and consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Televisions (Olson, 2013), and other household appliances (Sonnenberg et al, 2011), have been previously researched as products with significant environmental impact, as well as having characteristics associated with their production and use. To overcome any priming effect associated with asking consumers to complete a survey related to environmental attitudes, issues or specific environmental goods, we sought to target consumers who had recently purchased or were considering purchasing a plasma, LED or LCD television.…”
Section: Methods Sample Framementioning
confidence: 99%
See 1 more Smart Citation
“…Televisions (Olson, 2013), and other household appliances (Sonnenberg et al, 2011), have been previously researched as products with significant environmental impact, as well as having characteristics associated with their production and use. To overcome any priming effect associated with asking consumers to complete a survey related to environmental attitudes, issues or specific environmental goods, we sought to target consumers who had recently purchased or were considering purchasing a plasma, LED or LCD television.…”
Section: Methods Sample Framementioning
confidence: 99%
“…Kotler, 2011;Momberg et al, 2012;Rettie et al, 2012;do Paço et al, 2013;Culiberg, 2014). Economics suggests that individuals seek to maximize their own well-being (Steg and Vlek, 2009), such that only environmental attributes that enhance consumer value will impact the immediate purchase decision (Sonnenberg et al, 2011;Cleveland et al, 2012;Bartels and Onwezen, 2014). Economics suggests that individuals seek to maximize their own well-being (Steg and Vlek, 2009), such that only environmental attributes that enhance consumer value will impact the immediate purchase decision (Sonnenberg et al, 2011;Cleveland et al, 2012;Bartels and Onwezen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the respondents (N = 461) were females (n = 327/ 70.9%; males: n = 134/ 29.1%). A previous study that was done in the same geographic area (Sonnenberg et al, 2011) concluded that purchase decisions in this product category are mostly female driven although more than 40% of households engaged in joint decision-making.…”
Section: Methodsmentioning
confidence: 92%
“…The aim was to infer, on a horizontal continuum, products/services that consumers generally perceive as more complex and less complex than the anchoring product. A washing machine as an example of a major household appliance (MHA) that most households own, was specified as the anchoring product for the investigation based on evidence that is fairly challenging to purchase MHA (Donoghue et al, 2008;Sonnenberg et al, 2011) due to the multiple forms of risk that is associated with such purchase decision across most consumer segments (Nieftagodien and Van der Berg, 2007). It was presumed that the procedure would allow for a distribution of purchase decisions on either side of MHA on an envisaged complexity continuum.…”
Section: Measures and Analysesmentioning
confidence: 99%
“…Consumers can play a significant role in the mitigation of greenhouse gases due to their significant numbers (6.7 billion people) (Robinson, 2010), and their aggregate contribution to the increasing concentrations of these gases in the earth's atmosphere. A study of major household appliances purchases in South Africa supports this view point by stating that the environmental impact of an individual household's behaviour in terms of environment‐friendly appliance choices may be small but when many households implement such choices in the long term, their contribution to the environment becomes significant (Sonnenberg et al ., 2011). Consumers can also contribute to the mitigation of greenhouses via their purchasing vote by supporting ecologically sustainable businesses (Shaw et al ., 2006).…”
Section: Introduction: Consumers' Contribution To Global Warmingmentioning
confidence: 98%